Institutions, innovation, and industrialization : essays in economic history and development - Greif, Avner, 1955-; Kiesling, Laura Lynne, 1965-; Nye, John V. C. (Princeton University Press, 2015)
This book brings together a group of leading economic historians to examine how institutions, innovation, and industrialization have determined the development of nations. Presented in honor of Joel Mokyr--arguably the preeminent economic historian of his generation--these wide-ranging essays address a host of core economic questions. What are the origins of markets? How do governments shape our economic fortunes? What role has entrepreneurship played in the rise and success of capitalism? Tackling these and other issues, the book looks at coercion and exchange in the markets of twelfth-century China, sovereign debt in the age of Philip II of Spain, the regulation of child labor in nineteenth-century Europe, meat provisioning in pre-Civil War New York, aircraft manufacturing before World War I, and more. The book also features an essay that surveys Mokyr's important contributions to the field of economic history, and an essay by Mokyr himself on the origins of the Industrial Revolution. -- Provided by publisher.
Keywords: Economic history.; Histoire économique.; BUSINESS & ECONOMICS -- Economic History.; Economic history; Wirtschaftswissenschaften; Wirtschaft; Industrie; Ekonomisk historia.; Wirtschaftsgeschichte; Entwicklungstheorie; Industrialisierung; Institutionelle Infrastruktur; Innovation; Economics.